Cover Image, Volume 134, Issue 37. Issue 37 (5th October 2017) - Unknown
Abstract : This image from Francesco Piana and colleagues shows a FE‐SEM surface analysis of poly(2‐cyanoethyl vinyl ether) and a barium titanate (30 vol%) composite layer. Such material presents a high dielectric constant already with only 10 vol% of the filler while still keeping the electrical conductivity low. It has an application potential for ink‐jet printing in flexible organic electronics. (DOI:10.1002/app.45236 ).